Pengaruh Pemahaman Kode Etik Akuntan, Kecerdasan Emosional, dan Religiusitas terhadap Perilaku Etis Mahasiswa Akuntansi - Wiguna, I Komang Raditya; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 28 No 2 (2019), 2019)
The purpose of this study was to determine the effect of Understanding the Code of Ethics of  Accountants, Emotional Intelligence, and Religiosity on Ethical Behavior of Accounting  Students. This study uses multiple linear regression analysis techniques. In determining the  sample of this study using Slovin formula. From the calculation results, it was found that the  sample amounted to at least 75 respondents who were active students of the class of 2015  and had taken auditing courses 1. The type of data used in this study is quantitative data, in  the form of answers from respondents stated in the form of numbers from the questionnaire  was measured using a Likert scale. The results of the analysis show that the understanding  of the accountant's code of ethics, emotional intelligence, and religiosity positively  influences the ethical behavior of accounting students. Keywords:  Understanding of the accountant's code of ethics, emotional intelligence,  religiosity, ethical behavior.